Marketing and promoting electronic resources : creating the e-buzz! - Dubicki, Eleonora (Binghamton, NY : Haworth Information Press, 2009)
This books provides librarians with practical suggestions on how best to let their patrons know about the available e-resources, and instruct them on how to use them effectively.
"Co-published simultaneously as the serials librarian, volume 53, number 3, 2007."
Includes bibliographical references and index.
osa 03/06/2013
Loans
Keywords: Libraries; Academic libraries; Libraries and the Internet